The wisdom of Egypt : Jewish, early Christian, and gnostic essays in honour of Gerard P. Luttikhuizen - Hilhorst, A.; Kooten, Geurt Hendrik van, 1969-; Luttikhuizen, Gerard P. (Leiden ; Boston : Brill, 2005)
This collection of essays gives a vivid impression of Egypt as background and stage of Jewish, Christian, and Gnostic thought and life in antiquity. It demonstrates Egypt's important role in the history, literature and culture of these religions.
The disgrace of Egypt: Joshua 5.9a and its context / Ed Noort -- La Genèse d'Alexandrie, les Rabbins et Qumrân / Florentino García Martínez -- The birth of Moses in Egypt according to the Book of Jubilees (Jub 47.1-9) / Jacques T.A.G.M. van Ruiten -- Hearing the story of Moses in Ptolemaic Egypt: Artapanus accommodates the tradition / Rob Kugler -- Egypt as the setting for Joseph and Aseneth: accidental or deliberate? / János Bolyki -- The Wisdom of Solomon and the gnostic Sophia / Bert Jan Lietaert Peerbolte -- Cleopatra in Josephus: from Herod's rival to the wise ruler's opposite / Jan Willem van Henten -- 'The God who drowned the king of Egypt': a short note on an exorcistic formula / Pieter W. van der Horst -- 'Out of Egypt I have called my son': some observations on the quotation from Hosea 11.1 in Matthew 2.15 / Maarten J.J. Menken -- 'And Moses was instructed in all the wisdom of the Egyptians' (Acts 7.22) / Ton Hilhorst -- 'Wrath will drip in the plains of Macedonia': expectations of Nero's return in the Egyptian Sibylline oracles (book 5), 2 Thessalonians, and ancient historical writings / George H. van Kooten -- Looking at the condemning heart of 1 John 3.18-20 through the eyes of an ancient Egyptian / Herman te Velde -- The Egyptian background of the 'ointment' prayer in the Eucharistic rite of the Didache (10.8) / Huub van de Sandt -- The Letter of Barnabas in early second-century Egypt / Janni Loman -- Paul's rapture to paradise in early Christian literature / Riemer Roukema -- The Sphinx: sculpture as a theological symbol in Plutarch and Clement of Alexandria / John Herrmann and Annewies van den Hoek -- Foolish Egyptians: Apion and Anoubion in the Pseudo-Clementines / Jan N. Bremmer -- Potamiaena: some observations about martyrdom and gender in ancient Alexandria / Henk Bakker -- 'Mulier est instrumentum diaboli': women and the desert fathers / Monika Pesthy -- Le gnosticisme Alexandrin aux premiers temps du Christianisme / Attila Jakab -- The Gospel of Thomas and the historical Jesus: the case of eschatology / Albert L.A. Hogeterp -- Basilides of Alexandria: Matthias (Matthew) and Aristotle as the sources of inspiration for his gnostic theology in Hippolytus' Refutatio / Abraham P. Bos -- Early Christian apocrypha and the secret books of ancient Eygpt / Jacobus van Dijk -- Baraies on Mani's rapture, Paul, and the antediluvian apostles / Eibert Tigchelaar -- Devolution and recollection, deficiency and perfection: human degradation and the recovery of the primal condition according to some early Christian texts / F. Lautaro Roig Lanzillotta -- Reisewege der apostel in den Acta Petri aus Nag Hammadi / Jürgen Tubach -- The identity of Lithargoel in the Acts of Peter and the Twelve / István Czachesz -- Gnōsis, mageia, and The holy book of the great invisible spirit / Marvin Meyer -- Fate, magic and astrology in Pistis Sophia, chaps 15-21 / Jacques van der Vliet.
Includes bibliographical references (pages 537-547) and indexes.
Includes 2 contributions in French and 1 contribution in German.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Bible. -- Criticism, interpretation, etc; Luttikhuizen, Gerard P. -- Bibliographie; Bible. -- Critique, interprétation, etc; Bible; Egypt -- Religion; Égypte -- Religion; RELIGION -- History; TRAVEL -- Special Interest -- Religious; Religion; Egypt; Weisheit; Frühjudentum; Frühchristentum; Literatur; Ägypten; Gnosis; Vroege kerk; Jodendom; Gnosticisme; Festschriften; Criticism, interpretation, etc; Festschriften